2000
DOI: 10.1161/01.atv.20.7.1707
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Regulation of Free Radical– and Enzyme-Mediated Lipid and Lipoprotein Oxidation

Abstract: Abstract-The regulation of nonenzymatic and enzymatic lipid oxidation reactions by nitric oxide ( ⅐ NO) is potent and pervasive and reveals novel non-cGMP-dependent reactivities for this free radical inflammatory and signal transduction mediator. ⅐ NO and its metabolites stimulate and inhibit lipid peroxidation reactions, modulate enzymatically catalyzed lipid oxidation, complex with lipid-reactive metals, and alter proinflammatory gene expression. Through these mechanisms, ⅐ NO can regulate nonenzymatic lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(77 citation statements)
references
References 82 publications
1
71
0
5
Order By: Relevance
“…Therefore, it can be concluded that NO produced by iNOS mediates the endotoxin-induced increase in total antioxidant capacity and consequently decrease in lipid peroxidation. These results are also consistent with the observation that NO behaves as a potent antioxidant [21] . There are contradictory reports in the literature concerning role of NO as an antiinflammatory or proinflammatory agent [7,17,18] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it can be concluded that NO produced by iNOS mediates the endotoxin-induced increase in total antioxidant capacity and consequently decrease in lipid peroxidation. These results are also consistent with the observation that NO behaves as a potent antioxidant [21] . There are contradictory reports in the literature concerning role of NO as an antiinflammatory or proinflammatory agent [7,17,18] .…”
Section: Discussionsupporting
confidence: 93%
“…It is well known that oxidative stress results from an oxidant/antioxidant imbalance, an excess of oxidants and/or a depletion of antioxidants [4] . However, there are conflicting reports showing the effect of NO on lipid peroxidation [21,23] and oxidative stress [1,3,4] .…”
Section: Discussionmentioning
confidence: 99%
“…5 It is believed that oxidation of LDL may be modulated by nitric oxide (NO) and its products, as well as by myeloperoxidase and ceruloplasmin. 6,7 In one study, levels of oxidized LDL were significantly higher in patients with acute MI than in patients with angina or in controls, although lipid profiles did not differ among these groups. 8 In atherectomy specimens, the surface area containing macrophages that were positive for oxidized LDL was greater in patients with unstable angina than in those with stable angina.…”
Section: Inflammatory Mechanismsmentioning
confidence: 95%
“…When NO is in excess of surrounding oxidants, lipid oxidation and monocyte margination into the vascular wall are attenuated, producing antiatherogenic effects. However, when endogenous tissue rates of oxidant production are accelerated or when tissue oxidant defenses become depleted, NO gives rise to secondary oxidizing species that can increase membrane and lipoprotein lipid oxidation as well as foam cell formation in the vasculature, thus promoting proatherogenic effects (Bloodsworth et al, 2000). Therefore, targeting particularly upstream targets -substrates for oxidation and inflammation, will be important to better understand interactions of hyperlipidemia, inflammation and oxidation.…”
Section: Wwwintechopencom Oxidized Ldl and No Synthesis As Biomarkementioning
confidence: 99%